CAGE15-1 Cruise Report : CAGE-CO2 Winter Cruise to the western and northwestern Svalbard margin and the Barents Sea - Rasmussen, Tine L.; Zamelczyk, Katarzyna; Sztybor, Kamila; Ezat, Mohamed; Sørensen, Steffen Aagaard; Arnardóttir, Erna Ósk; Jonsdottir, Björg (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
From the afternoon of April 1st to the morning of April 9th 2015, CAGE at the Department of Geology Uit, the Arctic University of Norway, arranged a scientific cruise aimed at investigating the western Barents Sea slope, western and northern Svalbard margin, methane seep sites at Vestnesa and Storfjorden Trough and the Barents Sea on R/V “Helmer Hanssen”. Investigated areas were (in order of visiting sites on the cruise): Malangen Trough, Bjørnøya Trough Mouth Fan south and mid, Storfjorden Fan, Vestnesa Ridge, the northwest Svalbard slope to north of Schmeerenburgfjorden. On the track towards Tromsø we sampled in Storfjorden Trough. The scientific sampling was done within the framework of several ongoing projects at the Department of Geology, University of Tromsø: “CAGE -Centre for Arctic Gas hydrate, Environment and Climate”, in which the sub-projects “Paleo-CIRCUS”, “OA-Ocean Acidification” is included. A total of 2 gravity cores, 8 plankton net casts and 22 CTD (conductivity-temperature-depth) casts were performed along the route to Northern Svalbard at the western Barents Sea slope. Data were also collected in Storfjorden Trough and the mouth of Storfjorden. In addition, CTD’s and a small chirp and multibeam survey was performed off Schmeerenburgfjorden, north of fjorden and in its northernmost part. Chirp profiles and multibeam lines were acquired during transits and during the survey of outer Schmeerenburgfjorden. The recording started from c. 71 N on the western Barents Sea slope and ended at 70.00 N. The cruise may be known as: CAGE15_1_CO2